Morphological Plasticity of Emerging Purkinje Cells in Response to Exogenous VEGF - Herrfurth, Leonard; Theis, Verena; Matschke, Veronika; May, Caroline; Marcus, Katrin; Theiss, Carsten (Frontiers in Molecular Neuroscience, 2017)
Vascular endothelial growth factor (VEGF) is well known as the growth factor with wide-ranging functions even in the central nervous system (CNS). Presently, most attention is given to the investigation of its role in neuronal protection, growth and maturation processes, whereby most effects are mediated through VEGF receptor 2 (VEGFR-2). The purpose of our current study is to provide new insights into the impact of VEGF on immature and mature Purkinje cells (PCs) in accordance with maturity and related receptor expression. Therefore, to expand our knowledge of VEGF effects in PCs development and associated VEGFR-2 expression, we used cultivated organotypic cerebellar slice cultures in immunohistochemical or microinjection studies, followed by confocal laser scanning microscopy and morphometric analysis. Additionally, we incorporated in our study the method of laser microdissection, followed by quantitative polymerase chain reaction. For the first time we could show the age-dependent VEGF sensitivity of PCs with the largest promoting effects being on dendritic length and cell soma size in neonatal and juvenile stages. Once mature, PCs were no longer susceptible to VEGF stimulation. Analysis of VEGFR-2 expression revealed its presence in PCs throughout development, which underlined its mediating functions in neuronal cells.